The Challenge of Sustaining Ocean Observations - Weller, Robert A.; Baker, D. James; Glackin, Mary M.; Roberts, Susan J.; Schmitt, Raymond W.; Twigg, Emily S.; Vimont, Daniel J. (Frontiers in Marine Science, 2019)
Sustained ocean observations benefit many users and societal goals but could benefit many more. Such information is critical for using ocean resources responsibly and sustainably as the ocean becomes increasingly important to society. The contributions of many nations cooperating to develop the Global Ocean Observing System has resulted in a strong base of global and regional ocean observing networks. However, enhancement of the existing observation system has been constrained by flat funding and limited cooperation among present and potential users. At the same time, a variety of actors are seeking new deployments in remote and newly ice-free regions and new observing capabilities, including biological and biogeochemical sensors. Can these new needs be met? In this paper, a vision for how to sustain ocean observing in the future is presented. A key evolution will be to grow the pool of users, engaging end users across society. Users with shared values need to be brought together with commitment to sustainable use of the ocean in the broadest sense. Present planning for sustained observations builds on the development of the Global Ocean Observing System which has primarily targeted increased scientific understanding of ocean processes and of the ocean’s role in climate. We must build on that foundation to develop an Ocean Partnership for Sustained Observing that will incorporate the growing needs of a broad constituency of users beyond climate and make the case for new resources. To be most effective this new Partnership should incorporate the principles of a collective impact organization, enabling closer engagement with the private sector, philanthropies, governments, NGOs, and other groups. Steps towards achieving this new Partnership are outlined in this paper, with the intent of establishing it early in the UN Decade of Ocean Science.